Pengaruh Lama Perendaman Tomat Dalam Larutan Kalsium Hidroksida (Ca(Oh)2) Terhadap Sifat Organoleptik Dan Kadar Air Manisan Kering Tomat (Lycopersicum Esculentum Mill) - Mardila Ade Kantari; IKetut Swirya Jaya; Aladhiana Cahyaningrum (Jurnal Gizi Prima (Prime Nutrition Journal), 2016)
Background : Tomatoes are a better source of lycopene than raw tomatoes. Lycopene is known to have the ability as an antioxidant and can protect the body against various diseases, such as cancer and heart disease. Sweets is produced from fruit or vegetables preserved with sugar to prolong shelf life. Obstacles encountered in the manufacture of sweets are organoleptic properties, especially the soft texture of the fruit, and therefore the need for treatment by immersion in a solution of lime water. Of lime to sustain organoleptic properties, especially the soft texture of the fruit.  Objective : This study aimed to determine the effect of long immersion in a solution of calcium hydroxide tomatoes (Ca(OH)2) on the organoleptic properties and water content of dried candied tomatoes (Lycopersicum esculentum. Mill). Research Methods :This study used an experimental method with experiments in the laboratory. The design in this study was completely randomized design (CRD) with a single factor, namely long immersion treatment of tomatoes in a solution of calcium hydroxide, each re-treatment at 3 times, then performed organoleptic test and moisture test. Analysis of the data using analysis of variance (ANOVA) at α=0.05, while a further test using Tukey's test.  Results : Showing old tomato soaking in a solution of calcium hydroxide (Ca(OH)2) has significant effect on the color of candied dried tomatoes (p<0.05), while for the smell, taste and texture of candied dried tomatoes are not significant (p>0,05). Candied dried tomatoes are the most preferred is the treatment of candied dried tomatoes soaking for 4 hours. Long immersion in a solution of calcium hydroxide tomatoes (Ca(OH)2) significantly affected the moisture content of dried candied tomatoes (p<0.05) with the highest rates in the treatment t1 (22.6%) while the average lowest for the treatment t4 (18,3%).  Conclusion : Long immersion in a solution of calcium hydroxide tomatoes (Ca(OH)2) to the colors and candied dried tomato water content (p<0.05), while for the smell, taste and texture of candied dried tomatoes are not significant (p>0.05 )